Balancing Exploitation and Exploration Organizational Antecedents and Performance Effects of Innovation Strategies - Schulze, Patrick. (Gabler, 2009)
Recent case studies indicated that competing successfully in the present while simultaneously creating appropriate strategic options for the future is one of the toughest managerial challenges for established organizations. Patrick Schulze addresses this issue by investigating the performance effects and organizational antecedents of innovation strategies and, in particular, ambidexterity. He develops an interesting and innovative perspective on this question arguing that successful companies need to become ambidextrous by either the structural separation of existing and new business or the creation of a supportive organizational context.